U.S. Navy special forces : SEAL teams - Burgan, Michael (Mankato, Minn. : Capstone Books, 2000)
Introduces the Navy special forces known as SEALs, describing their mission, history, and the equipment they use.
Includes bibliographical references and index.
L0740
Keywords: United States. -- Navy. -- SEALs; United States. -- Navy -- Commando troops; Special operations (Military science)